Nivolumab for Relapsed/Refractory Classic Hodgkin Lymphoma After Failure of Autologous Hematopoietic Cell Transplantation: Extended Follow-Up of the Multicohort Single-Arm Phase II CheckMate 205 Trial - Armand, Philippe; Engert, Andreas; Younes, Anas; Fanale, Michelle; Santoro, Armando; Zinzani, Pier Luigi; Timmerman, John M; Collins, Graham P; Ramchandren, Radhakrishnan; Cohen, Jonathon B; De Boer, Jan Paul; Kuruvilla, John; et al. (Journal of clinical oncology, 2018)
Purpose Genetic alterations causing overexpression of programmed death-1 ligands are near universal in classic Hodgkin lymphoma (cHL). Nivolumab, a programmed death-1 checkpoint inhibitor, demonstrated efficacy in relapsed/refractory cHL after autologous hematopoietic cell transplantation (auto-HCT) in initial analyses of one of three cohorts from the CheckMate 205 study of nivolumab for cHL. Here, we assess safety and efficacy after extended follow-up of all three cohorts. Methods This multicenter, single-arm, phase II study enrolled patients with relapsed/refractory cHL after auto-HCT treatment failure into cohorts by treatment history: brentuximab vedotin (BV)-naïve (cohort A), BV received after auto-HCT (cohort B), and BV received before and/or after auto-HCT (cohort C). All patients received nivolumab 3 mg/kg every 2 weeks until disease progression/unacceptable toxicity. The primary end point was objective response rate per independent radiology review committee. Results Overall, 243 patients were treated; 63 in cohort A, 80 in cohort B, and 100 in cohort C. After a median follow-up of 18 months, 40% continued to receive treatment. The objective response rate was 69% (95% CI, 63% to 75%) overall and 65% to 73% in each cohort. Overall, the median duration of response was 16.6 months (95% CI, 13.2 to 20.3 months), and median progression-free survival was 14.7 months (95% CI, 11.3 to 18.5 months). Of 70 patients treated past conventional disease progression, 61% of those evaluable had stable or further reduced target tumor burdens. The most common grade 3 to 4 drug-related adverse events were lipase increases (5%), neutropenia (3%), and ALT increases (3%). Twenty-nine deaths occurred; none were considered treatment related. Conclusion With extended follow-up, responses to nivolumab were frequent and durable. Nivolumab seems to be associated with a favorable safety profile and long-term benefits across a broad spectrum of patients with relapsed/refractory cHL.
Keywords: výsledek terapie; Male; imunokonjugáty; nivolumab; lokální recidiva nádoru; Antineoplastic Agents, Immunological; následné studie; Kaplan-Meier Estimate; Europe; Adult; transplantace hematopoetických kmenových buněk; Kaplanův-Meierův odhad; dospělí; Immunoconjugates; mužské pohlaví; protinádorové látky imunologicky aktivní; Nivolumab; Follow-Up Studies; Hodgkin Disease; Treatment Outcome; Evropa; Neoplasm Recurrence, Local; lidé; ženské pohlaví; Humans; North America; Hodgkinova nemoc; Female; lidé středního věku; Hematopoietic Stem Cell Transplantation; Middle Aged; Severní Amerika